Blue Light Irradiation Induces Human Keratinocyte Cell Damage via Transient Receptor Potential Vanilloid 1 (TRPV1) Regulation. (16th December 2020) - Yoo, Ju Ah.; Yu, Eunbi; Park, See-Hyoung; Oh, Sae Woong; Kwon, Kitae; Park, Se Jung; Kim, Hyeyoun; Yang, Seyoung; Park, Jung Yoen; Cho, Jae Youl; Kim, Youn-Jung; Lee, Jongsung
Abstract : Although blue light has been reported to affect skin cells negatively, little is known about its action mechanisms in skin cells. Therefore, we investigated the role of the transient receptor potential vanilloid 1 (TRPV1) in blue light-induced effects on human keratinocytes and its underlying mechanisms. Blue light decreased cell proliferation and upregulated TRPV1 expression. Blue light also suppressed the epidermal growth factor receptor- (EGFR-) mediated signaling pathway by reducing the protein levels of EGFR and suppressing the EGFR/PI3K/AKT/GSK3 β /FoxO3a pathway. The blue light-induced effect in cell proliferation was reversed by TRPV1 siRNA, but not capsazepine, a TRPV1-specific antagonist. In addition, blue light irradiation increased the production of reactive oxygen species (ROS) and tumor necrosis factor- α (TNF- α ). Blue light irradiation also increased both phosphorylation levels of TRPV1 and calcium influx. The blue light-induced increase in production of ROS and TNF- α was reversed by capsazepine. Furthermore, the blue light-induced increase in production of TNF- α was attenuated by SP600125 or PDTC. These findings show that blue light regulates cell survival and production of ROS and TNF- α ; its effects are mediated via TRPV1. Specifically, the effects of blue light on cell proliferation are mediated by upregulating TRPV1, a negative regulator of EGFR-FoxO3a signaling. Blue light-induced production of ROS and TNF- α is also mediated through increased calcium influx via TRPV1 activation.